Analysis and design of single-span integral bridge members using strut-and-tie modeling approach - Banerjee, Supriya; Saini, Kusum; Matsagar, Vasant A. (Journal of Structural Engineering, 2024)
The use of Carbon Fiber-Reinforced Polymers (CFRP) for reinforcing and prestressing concrete structures is apromising alternative in the infrastructure industry. Particularly, prestressed concrete members reinforced with suchpolymeric materials are becoming popular to evade corrosion-related issues. The conventional simply supported bridgerequires bearings and expansion joints for various load transfers, mandating regular maintenance and protectionfrom corrosion. The corrosion-related distress and additional joints directly or indirectly reduce the bridge life andincrease the cost as well as maintenance activities. To avoid such challenges, the present study proposes the design of anintegral bridge with reinforced and prestressed fiber-reinforced composite tendons alternative to the traditional simplysupported bridge reinforced with corrosion-prone steel rebars. Herein, the Strut-and-Tie Modeling (STM) approach isfollowed for the analysis of the integral bridge members. Furthermore, the design of the integral bridge based on theSTM approach is compared with the traditional limit state design approach. A full-scale three-dimensional (3D) FiniteElement (FE) model of a CFRP composite-reinforced single-span integral bridge is developed. Stress field analysis isperformed corresponding to Ultimate Limit State (ULS) combinations as per the EN 1990 Eurocode. Also, topologyoptimization of an idealized portal frame of the bridge is performed for the applied vertical loading on the structure.The optimized truss topology has proven helpful in reducing computational cost and time requirements using the STMapproach.